(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the impact of ESG policies on bank profitability. It is substantiated that in modern conditions it is advisable for banks to balance when making decisions on providing loans between traditional borrowers and companies of the "green" economy, bearing in mind that the risks of climate change affect the activities of economic entities in different ways. Conclusions are made that the development of corporate clients of banks in accordance with the principles of environmental, social and corporate governance (ESG) will have a positive effect on the financial results of companies and the sustainability of banks.